Directed Expression of Tracheal Antimicrobial Peptide as a Treatment for Bovine-Associated Staphylococcus Aureus-Induced Mastitis in Mice - Zhang, Zhipeng; Chen, Daijie; Lu, Xubin; Zhao, Ruifeng; Chen, Zhi; Li, Mingxun; Xu, Tianle; Mao, Yongjiang; Yang, Yi; Yang, Zhangping (Frontiers in Veterinary Science, 2021)
Bovine mastitis is perplexing the dairy industry since the initiation of intensive dairy farming, which has caused a reduction in the productivity of cows and an escalation in costs [1]. The use of antibiotics causes a series of problems, especially the formation of bacterial antimicrobial resistance [2]. However, there are limited antibiotic-free therapeutic strategies that can effectively relieve bacterial infection of bovine mammary glands. Hence, in this study, we constructed a mammary gland tissue-specific expression vector carrying the antimicrobial peptide of bovine-derived tracheal antimicrobial peptide (TAP) and evaluated it in both primary bovine mammary epithelial cells (pBMECs) and mice. The results showed that the vector driven by β- lactoglobulin gene (BLG) promoter could efficiently direct the expression of TAP in pBMECs and the mammary gland tissue of mice. In addition, significant antibacterial effects were observed in both in vitro and in vivo experiments when introducing this vector to bovine-associated Staphylococcus aureus treated pBMECs and mice, respectively. This study demonstrated that the mammary gland tissue-specific expression vector could be used to introduce antimicrobial peptide both in in vitro and in vivo, and will provide a new therapeutic strategy in the treatment of bovine mastitis.